Shear wave splitting of the 2018 Lombok earthquake aftershock area, Indonesia - Annisa Trisnia Sasmi (2023)
Lombok is one of the islands in the transitional zone from the Sunda Arc to the Banda Arc, Indonesia. In the mid-2018, the island of Lombok was shaken by a series of strong earthquakes, started with a moment magnitude (Mw) 6.4 earthquake on July 29, 2018 followed by earthquakes on August 5 (Mw 7.0), August 9 (Mw 5.9), and August 19 (Mw 6.3 and 6.9). Some researchers suggested that this phenomenon occurred due to a segmentation rupture in the northern part of Lombok Island. This study aims to obtain information on the distribution of the Lombok earthquake fault zone 2018 and also to understand the character of seismic anisotropy around the Lombok earthquake fault zone 2018 through Shear Wave Splitting (SWS) study. Splitting, or S-wave separation, occurs when the S wave passes through an anisotropic medium. The S wave is split into fast and slow S waves with almost orthogonal polarizations and has parameters such as delay time and polarization direction of the fast S wave. To determine the SWS parameters, we used a Lombok earthquake aftershock data set recorded from 4 August to 9 September 2018, using 16 seismographic stations. The steps taken to obtain the SWS parameters are event selection, windowing using short time Fourier transform, and rotation-correlation process. The results of the SWS analysis indicate that the fast polarization directions probably have a linkage with the local fault system and the fault related to the Lombok earthquake fault zone.